Synthesis of Antioxidant Stabilizers AO-1, Their Application to Polyethylenes, IR Spectral and Thermogravimetric Analysis of Stabilized Polyethylenes - Karaev Sherali; Djalilov Abdulakhat; Karimov Masud, (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The synthesis of the antioxidant stabilizer AO-1 was carried out in three stages. Medium-density polyethylene products were mixed with PY-342 using the CLAWSON method and processed in a Jinan Himax LSB extruder to determine the properties of the synthesized antioxidant stabilizer for stabilizing polyethylene products. In the IR spectrum of stabilized polyethylenes, asymmetric and symmetric stretching vibrations of the methyl (-CH3) and methylene (-CH2) groups were obtained in the region of 2848-2914 cm-1 of the spectrum and the presence of phenol homologues was determined in the region of 1700-2000 cm-1. It was found that low-intensity lines are characteristic of rotational and pendulum vibrations of the methylene group and are located in the region of 1305 and 717 cm-1, and stabilized polyethylene was analyzed using thermogravimetric analysis. The decomposition of polyethylene occurs at a temperature of 120°C, and the decomposition of polyethylene with the addition of the antioxidant stabilizer AO-1 occurred at a temperature of 380.57°C. In this case, a mass loss of 0.053 mg or 1.897% occurs, which indicates an improvement in the physicochemical properties of polyethylene.